2020
DOI: 10.1080/12298093.2020.1843221
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Pinkish Brown-Spored Neotropical Boletes:Austroboletus subflavidusandFistulinella gloeocarpa(Boletaceae, Boletales) from the Dominican Republic

Abstract: The occurrence of Austroboletus subflavidus and Fistulinella gloeocarpa is documented from the Dominican Republic. The latter species is reported for the first time outside its original locality in Martinique, extending the geographic range for this uncommon pinkish-spored bolete. A detailed morphological description is provided for each species and accompanied by color pictures of fresh basidiomes in habitat and line drawings of the main anatomical features. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
3
8
0
Order By: Relevance
“…The clustering of some Austroboletus gracilis sequences within the Veloporphyrellus is also dubious. Similar findings were also reported by Wu et al (2016) and Gelardi et al (2020). As suggested by Wu et al (2016), these sequences of A. gracilis might represent a Veloporphyrellus species submitted with wrong identity.…”
Section: Similar Speciessupporting
confidence: 87%
See 1 more Smart Citation
“…The clustering of some Austroboletus gracilis sequences within the Veloporphyrellus is also dubious. Similar findings were also reported by Wu et al (2016) and Gelardi et al (2020). As suggested by Wu et al (2016), these sequences of A. gracilis might represent a Veloporphyrellus species submitted with wrong identity.…”
Section: Similar Speciessupporting
confidence: 87%
“…According to the studies of Wu et al (2016) and Gelardi et al (2020), Velporphyrellus is polyphyletic. Li et al (2014) also reported that species of Veloporphyrellus nested within three different clades.…”
Section: Similar Speciesmentioning
confidence: 99%
“…Moreover, A. brunneisquamus is also morphologically similar to A. dictyotus, A. fusisporus and A. subflavidus (Murrill) Wolfe. However, A. dictyotus, originally discovered in Indonesia, has a larger basidioma (pileus up to 11 cm), larger basidiospores measuring (11-)13-16 × (6-)7-8.5 μm with reticulations, and a pileipellis in the form of a trichoderm [1,2]; A. fusisporus, originally discovered in Japan, has a smaller pileus with a viscid surface, large basidiospores measuring 13.5-18.5 × 8-11 μm with subcylindrical ornamentation, and a trichodermium pileipellis [1,43]; A. subflavidus has longer basidiospores measuring 13.1-19.5 × 5.5-8.7 μm with Qm = 2.26, a pileipellis in the form of a trichoderm, and a distribution in North America-Central America-northern South America [5]. Molecular evidence provided in this study also indicated that A. brunneisquamus is genetically distant from A. dictyotus and A. fusisporus, respectively, and it is somewhat related to A. subflavidus, as these two taxa belong to the same clade (not species level) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Austroboletus (Corner) Wolfe (Boletaceae, Boletales), typified by A. dictyotus (Boedijn) Wolfe, is characterized by a pinkish pore surface at maturity, context usually unchanging in color when injured, a stipe, often with conspicuous reticulation, fusiform or amygdaliform basidiospores with verrucose, warted, irregularly pitted, cristate, subcylindrical, ridged or subreticulate ornamentations, and forming ectomycorrhizae with Fagaceae, Pinaceae and Dipterocarpaceae [1][2][3][4][5]. Species of Austroboletus are mostly distributed in tropical regions [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various authors ( Wu et al 2014 ; Wu et al 2016 ; Gelardi et al 2020 ; Kuo and Ortiz-Santana 2020 ) have recognised the polyphyly of Austroboletus , which is divided into the Austroboletus s.s., Austroboletus s.l. and the A.…”
Section: Introductionmentioning
confidence: 99%